ASSESSMENT OF INFLUENCE OF BETAGISTIN IN COMBINATION WITH ANTIHYPERTENSIVE DRUGS ON QUALITY OF LIFE AND NEUROLOGICAL STATUS OF PATIENTS WITH STABLE ARTERIAL HYPERTENSION AND DIZZINESS - G. V. Andreeva; S. Y. Martsevich; V. M. Gorbunov; O. A. Melnikov; V. P. Voronina; I. P. Zhigareva (Рациональная фармакотерапия в кардиологии, 2015)
More than a half of patients with stable mild to moderate arterial hypertension (AH) have dizziness. Rather often these patients need to take drugs, reducing blood pressure (BP) in combination with those, reducing intensity of dizziness. As patients with stable AH have bad compliance with the treatment, it is necessary to consider not only drug efficiency, but also its influence on quality of life (QL).Aim. To assess influence of combined therapy with betagistin hydrochlorid and lisinopril on QL and neurological status of patients with stable mild to moderate AH.Material and methods. 67 patients with stable AH of I-II grades, risk 2-3 and medium intensity of dizziness took part in randomized, cross over design, placebo-controlled study. After 2 weeks of “wash-out” period all patients received lisinopril alone or lisinopril in combination with betagistin. Every therapy regimes lasted 1 mouth. Evaluation of QL, intensity of dizziness, daily BP was made before and at the end of each therapy regimes, evaluation of neurological status – before and at the end of the first therapy regime.Results. Therapy with both schemes of treatment resulted in comparable decrease in BP level. Treatment with both regimes relieved dizziness and concomitant symptoms. Combined therapy with betagistin and lisinopril showed improvement of almost all the elements of QL, while monotherapy with lisinopril – of only several ones. Combined treatment with lisinopril and betagistin had more favorable influence on QL, and neurological status.Conclusion. The main reason, which caused dizziness in patients with stable AH, was chronic double-sided changes in vestibular system. Combined treatment with lisinopril and betagistin had more positive influence on QL and neurological status than monotherapy with lisinopril. BP decrease according to the two schemes of therapy was comparative in both therapy regimes.